Microwave assisted extraction of pectin from dried hull of faba bean - Shams, Rafeeya; Masih, Dorcus; Ashraf, Ghousia; Dar, Aamir Hussain; Rizvi, Qurat ul eain Hyder (Journal of Postharvest Technology, 2020)
This study intended to estimate the potential uses of faba bean hull as pectin source for various commercial applications such as gelling, thickening,  stabilization etc. The extraction was carried out at microwave power (160–640 W), time (3–12 min), pH (1.5) and solid: liquid ratio (1:20 g/ml). The  optimal conditions of microwave assisted extraction to yield high pectin from faba bean hull powder (14.86 %) were found to be at pH 1.5, microwave  power of 640 W, extraction time of 9 min, solvent: solid ratio of 1:20 g/ml respectively. The pectin extracted was characterized as high methoxylpectin  with anhydrous acid content and methoxyl content of 51.38% and 4.89% respectively and degree of esterification 54.08%. The extracted pectin  depicted equivalent weight, anhydrouronic acid content and methoxyl content of 746.26%, 51.38% and 4.89% respectively. As little information is  present on extraction of pectin from faba bean hull. The present study revealed that faba bean hull is better and suitable pectin source and considered  to be the potential raw material for various food processing applications.
Keywords: Faba bean hull; equivalent weight; methoxyl content; pectin; degree of esterification